The Level of Job Satisfaction among Staff Nurses Working in Hospital: Exploring the Link between Compensation and Job Satisfaction in the Hospital Sector (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Keeping your employees around is crucial to your company's long-term health. The focus ofthis study was on the healthcare industry in Jaipur, and specifically on the correlation betweencompensation and work satisfaction. Few studies have looked at how compensation, benefits, and jobsatisfaction are linked, and contentment in the hospital sector throughout the nation. To see howincentives fare in drawing and keeping elite talent, researchers turned to quantitative analysis. Explanatoryhypotheses were developed utilizing a survey strategy and a semi-structured questionnaire. Workerperformance and job satisfaction were both shown to be directly affected by pay, whereas jobsatisfaction was found to have a negative impact on worker performance and play no mediating functionbetween pay and output.